2007
DOI: 10.1016/j.brainres.2007.04.057
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor-mediated extracellular adenosine accumulation is blocked by phosphatase 1/2A inhibitors

Abstract: We have previously demonstrated that NMDA receptor-mediated extracellular adenosine accumulation in neuronal cultures is receptor-mediated and requires calcium influx. Because protein kinase C (PKC) is a calcium-dependent enzyme, we hypothesized that activation of PKC might be involved in NMDA-mediated adenosine accumulation. PKC inhibitors however, did not block NMDA-evoked adenosine accumulation, but rather, stimulated basal adenosine accumulation. These data suggested the possibility that NMDA receptor medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…These results suggest that modified-HLJDD may improve dysfunctional ATP metabolism and ameliorate the oxidative stress and mitochondrial dysfunction in AD model, which may be partially explained by modified-HLJDD suppressing reactive microgliosis and astrogliosis in the hippocampus of AD model. We conclude that these two mechanisms may be linked, since NMDA receptors can decrease adenosine kinase activity and evoke adenosine accumulation [59, 60], and adenosine can also regulate glutamatergic transmission [61]. According to this previous study and the results of the present study, NMDA receptors were decreased in the hippocampus in AD model, and we also concluded that the downstream adenosine pathway may also be decreased.…”
Section: Discussionsupporting
confidence: 64%
“…These results suggest that modified-HLJDD may improve dysfunctional ATP metabolism and ameliorate the oxidative stress and mitochondrial dysfunction in AD model, which may be partially explained by modified-HLJDD suppressing reactive microgliosis and astrogliosis in the hippocampus of AD model. We conclude that these two mechanisms may be linked, since NMDA receptors can decrease adenosine kinase activity and evoke adenosine accumulation [59, 60], and adenosine can also regulate glutamatergic transmission [61]. According to this previous study and the results of the present study, NMDA receptors were decreased in the hippocampus in AD model, and we also concluded that the downstream adenosine pathway may also be decreased.…”
Section: Discussionsupporting
confidence: 64%
“…Inhibition of protein phosphatases reduces postsynaptic signaling as a major mechanism for basal synaptic transmission and memory formation [84]. It has been reported that inhibition of protein phosphatases increases tau phosphorylation and initiates neuronal cell death which includes altered Ca 2+ homeostasis and glutamate excitotoxicity that alter the memory formation [85, 86]. Previous reports suggested that accumulation and mislocalization of hyperphosphorylated tau in the somatodendritic compartment of neurons in AD disrupts glutamate receptor trafficking and synaptic function [8789].…”
Section: Phosphatase Inhibition Nmda Receptor Tau Hyperphosphorylatmentioning
confidence: 99%
“…NMDA‐R activation might play an important role in regulation of excitotoxicity (Lu and Rosenberg, ) of mammalian brains in several types of neurotoxicity and other type of cell toxicity (Nicholls et al, ) and mainly involving NMDA‐R. Disrupted Ca 2+ homeostasis and recruitment of reactive oxygen/nitrogen species (ROS/RNS) leads to oxidative/nitrosative stress through NMDA‐R activation (Sas et al, ).…”
Section: Discussionmentioning
confidence: 99%